2006
DOI: 10.1103/physrevlett.97.260403
|View full text |Cite
|
Sign up to set email alerts
|

Bogoliubov-Čerenkov Radiation in a Bose-Einstein Condensate Flowing against an Obstacle

Abstract: We study the density modulation that appears in a Bose-Einstein condensate flowing with supersonic velocity against an obstacle. The experimental density profiles observed at JILA are reproduced by a numerical integration of the Gross-Pitaevskii equation and then interpreted in terms ofCerenkov emission of Bogoliubov excitations by the defect. The phonon and the single-particle regions of the Bogoliubov spectrum are respectively responsible for a conical wavefront and a fan-shaped series of precursors.PACS num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
154
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(168 citation statements)
references
References 21 publications
11
154
1
2
Order By: Relevance
“…For the same reasons that polaritons benefit from unusually favourable features for condensation, such as very high critical temperatures, it is expected that their superfluid properties would likewise manifest with altogether different magnitudes, such as very high critical velocities. Since they have shown many deviations in their Bose-condensed phase from the cold atoms paradigm, it is not clear a priori to which extent their superfluid properties would coincide or depart from those observed with atoms, among which quantised vortices 6 , frictionless motion 7 , linear dispersion for the elementary excitations 8 , or more recently Čerenkov emission of a condensate flowing at supersonic velocities 9 , are among the clearest signatures of quantum fluid propagation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reasons that polaritons benefit from unusually favourable features for condensation, such as very high critical temperatures, it is expected that their superfluid properties would likewise manifest with altogether different magnitudes, such as very high critical velocities. Since they have shown many deviations in their Bose-condensed phase from the cold atoms paradigm, it is not clear a priori to which extent their superfluid properties would coincide or depart from those observed with atoms, among which quantised vortices 6 , frictionless motion 7 , linear dispersion for the elementary excitations 8 , or more recently Čerenkov emission of a condensate flowing at supersonic velocities 9 , are among the clearest signatures of quantum fluid propagation.…”
mentioning
confidence: 99%
“…At a given time t I , we release a Gaussian pulse (F I ≠0) that triggers OPO processes. We track the new evolution of ψ(x,t) until the steady state is restored, barrier at Mach numbers greater than one 9 . It is important to note that the visibility of these waves does not imply that the signal polaritons are also in the "Čerenkov" regime.…”
mentioning
confidence: 99%
“…Finally, in a broader context, one expects other situations that generate a scattered atom halo, such as molecular dissociation in a condensate [36,37,[42][43][44][45][46][47][48], atomic parametric down-conversion [4,[49][50][51][52][53], or the interaction of a condensate with barriers and obstacles [54][55][56][57][58], to also be susceptible to the same anisotropy-producing processes. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been considerable interest in the investigation of the effects of a moving obstacle (or object) through a Bose-Einstein condensed system in various trapping geometries [1][2][3][4][5][6][7][8][9]. The obstacle is a potential barrier generated by a Gaussian laser beam [3,8], which can be repulsive or attractive depending on the wavelength of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…The obstacle is a potential barrier generated by a Gaussian laser beam [3,8], which can be repulsive or attractive depending on the wavelength of the beam. Previous work has also shown that the motion of this obstacle, whether linear or rotational, causes excitations leading to strikingly interesting phenomena such as vortices [1,[10][11][12][13][14], solitons [12,15], crescent vortex solitons [16], and dispersive waves accompanying the solitons [17].…”
Section: Introductionmentioning
confidence: 99%